Bitrix24 as an effective automated system of document projects management - Tievikova, Olha; Lysenko, Alla (Видавництво Львівської політехніки, 2019)
Implementation of project management into business sphere allows quickly and efficiently react on changing conditions of external market and social environment, helps to create a variety of projects and programs, promotes growth of the manufacturing process productivity and performance. It is worth mentioning Ukrainian corporate projects management system with broad functional capabilities of Bitrix24. Their software product offers one of the best CRM-systems, which includes more than 40 modules for various tasks solving. These are tools for project participants communication and interaction, electronic workflow, analytics performance, marketing etc.
Keywords: automated system; electronic workflow; program; project management; software support